Applicability of a canine prostate simulator (PROSIM-DOG) in clinical veterinary practices - Matilla-Pinto, Elvira; Balao da Silva, Carolina (Frontiers in Veterinary Science, 2025)
Simulators help students to perform procedures as many times as needed, in a controlled and non-stressful environment. It is crucial to include transrectal digital palpation in the physical examination of dogs for effective clinical diagnosis of prostate diseases, since this is a commonly found pathology in intact males. Training in prostate palpation may be hindered if students cannot assess and compare different types of prostates, a common situation that can be solved by training devices. A low-cost canine prostate simulator (PROSIM-DOG) was developed and tested by 167 veterinary science students, in order to compare their perspective and usefulness of the simulator. Students were divided into four groups with varying levels of instructional support. Group 1 (n = 35) received a technique description, used the simulator, and completed two questionnaires (simulator and real examination). Group 2 (n = 35) received a description, visual aids, and palpated inert prostates without the simulator before the live exam. Group 3 (n = 36) received only a written description before the live exam. Group 4 (n = 61) had access to a description, inert prostates, the simulator, and completed the questionnaire to assess device applicability. Additionally, fourteen faculty members also answered a third questionnaire, in order to validate PROSIM-DOG. Students with access to images and simulator palpation (group 2) achieved higher diagnostic accuracy (66.6%), while most in the description-only group (group 3) reported uncertainty during examination (80%) and considered the teaching method insufficient (77.7%). Overall, all students positively evaluated the device and considered that it significantly improved their understanding of canine prostatic anatomy and pathology, increased confidence to perform transrectal digital palpation in dogs and that it reduced their anxiety associated with first-time clinical procedures. Enquired faculty members endorsed the simulator's educational value, emphasizing its potential to standardize practical training. Fourteen faculty members also answered a third questionnaire, endorsed the simulator's educational value, emphasizing its potential to standardize practical training. These findings support the integration of PROSIM-DOG into veterinary curricula as a valuable tool for both preclinical preparation practices and skill reinforcement in clinical rotations. Future research should focus on longitudinal studies assessing the impact of simulators on student performance and diagnostic accuracy in real clinical contexts.